The Applicability of a Scale on Self-Regulated Writing Strategies in English for High School Students - Teresa Angelina Kaluge; Sisilia Setiawati Halimi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Writing appeared to be crucial in learning foreign languages. This study aimed at examining the applicability of a measure on self-regulated writing strategies in terms of its psychometric properties. The scale items were designed from theoretical foundations and previous relevant studies. Questionnaires were distributed online to high school students, collected and analyzed as many as 106. Correlation, confirmatory factor analyses, and calculating Cronbach’s alpha were carried out to make sure the applicability of the scale. The findings showed five main constructs to be applicable. They were self-initiating, planning, text-generating, revising, and acting on feedback.